PENGARUH KARTU MEMBER TERHADAP PENINGKATAN OMSET PENJUALAN PT. PRIMAGRAPHIA DIGITAL PRINTING CABANG BOGOR - Eka Tiarni Hutajulu; Puja Rizqi Ramadhan; Mika Debora Barus (Ensiklopedia Education Review, 2022)
The purpose of writing this article is to determine the role of Member Cards in increasing Sales Turnover of PT. Primagraphia Digital Printinh Bogor Branch. Currently, financial difficulties make people wiser in using their finances, for example by choosing buy products eith bigger discounts, in general, many discounted are given to member card holders. This study focuses on how the benefits of ownership of member cards provided by the company for consumers in increasing salaes of PT. Primagraphia Digital Printing, especially in the Bogor branch. The methodology used is a qualitative research methodology.Keywords: Costumer Satisfaction, Discount, Member Card, and Sales Turnover.